Stigma experienced by families of individuals with intellectual disabilities and autism: A systematic review - Mitter, Natasha; Ali, Afia; Scior, Katrina (Research in developmental disabilities, 2019)
Studies have investigated the experiences of courtesy stigma and affiliate stigma in family members of individuals with intellectual and developmental disabilities (IDD) without a clear distinction between the two. This systematic literature review aimed to evaluate the findings of studies that examined the experiences of stigma in families of individuals with intellectual disabilities and/or autism. A systematic search of PsycINFO, ERIC and Scopus identified relevant articles published between 2012 and 2016, to expand on an earlier review on this topic published in 2012. Ten articles pertaining to eight studies were identified. They revealed that family carers do experience stigma and various consequences related to these, with family culture influencing these experiences. This review identifies a number of psychosocial variables that are associated with the development of courtesy stigma, affiliate stigma and their consequences. It highlights protective factors and strategies family carers use to cope with stigma, and a lack of clarity in distinguishing the concepts of courtesy stigma and affiliate stigma in family members.